Supperior Fishing Gear for Coral Reef Fishes in Western Seram Regency - Tupamahu, Agustinus; Haruna, Haruna; Hutubessy, Barbara G; Siahainenia, Stany R; Nanlohy, Albert Ch; Hehanusa, Kedswin (Sangia Research Media and Publishing, 2021)
Various fishing gears that are operated in the coral reef waters of Western Seram Regency have their own selectivity, capture various species of fish, and have an impact on the damage to coral reef ecosystems. This study aims to determine the leading reef fishing gears in Western Seram District. The survey method is through observations and interviews with fishermen who conduct fishing activities of coral species. Respondents are determined by propulsive sampling, the selection of superior fishing gear is done by the scoring method. The results showed that the fishing gear classified into the line fishing gear was superior to other fishing gear, where the bottom trolling were superior. The less favored coral fishing equipment especially from the biological aspect needs attention to improve the method and design of the fishing gear.